KEPATUHAN WARTAWAN TERHADAP KODE ETIK JURNALISTIK DI KOTA PALANGKA RAYA - Rachmat Hidayat; Idiannor Mahyudin; Mardiana Mardiana (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2014)
Each of Indonesian journalists must uphold the Code of Journalistic Ethics in carrying out any work in the field of journalism . However, this time not all Indonesian journalists make journalism ethics as a